Lingupoetics Of Free Indirect Speech: Brief Analysis - Siddikova, Shokhida Isokovna (International Journal of Psychosocial Rehabilitation, 2020)
In world linguistics, the interest in the syntactic nature of direct, and reported speech has never faded. Recently, there has been an increase in research on indirect speech and the issue of its placement in the text has long been in the spotlight of researchers.In world linguistics, it has been recognized that the linguistic nature of linguistic units is not immanent, but that the speech situation in which these units are used has the potential to draw new conclusions by studying within a particular text. In this sense, one of the most important issues in linguistics is the study of indirect speech and its types within a particular text, to determine the communicative, pragmatic and linguopoetic features, to reveal the linguopoetic possibilities of indirect sentences and to determine their place in the system of compound sentences.Special attention was paid to the education system in order to inculcate in the minds of the younger generation the achievements of the independence period, science and science, literature and art, culture and spirituality, changes in production, the scale of achievements. Although a number of achievements have been made in the study of various levels of the Uzbek language, there are still many tasks to be performed. One of them is the study of the syntax and linguopoetics of the Uzbek language, and some work on this issue in has been made in linguistics. made. However, they do not suficiently define the methods of introducing indirect speech into the literary text and the communicative-syntactic and linguopoetic possibilities of indirect speech forms. Clearly, it is dificult to imagine the development of education without a more in-depth study of the inherent laws of language and without an objective interpretation of aspects inherent in its immediate nature. Therefore, all manifestations of the expression of the indirect speech and its peculiarities as a separate object of study and, of course, require special study within the text.